Fabricating GaN-based LEDs on (−2 0 1) β-Ga2O3 substrate via non-continuous/continuous growth between low-temperature undoped-GaN and high-temperature undoped-GaN in atmospheric pressure metal-organic chemical vapor deposition. (19th September 2019) - Lan, Yu-Pin; Chen, Yen-Chun; Yeh, Yi-Yun; Hung, Shun-Ming
Abstract: This study demonstrates two approaches to the growth of GaN-based LEDs on (−2 0 1)-oriented β -Ga2 O3 single crystal substrates using metal-organic CVD under atmospheric pressure. One approach induces non-continuous growth between low-temperature undoped-GaN (u-GaN) and high-temperature u-GaN, whereas the other approach induces continuous growth. We observed the following reduction in the FWHM of X-ray diffraction rocking curves: GaN (0 0 2) on (−2 0 1) β -Ga2 O3 substrate (from 464 to 342 arcsec) and GaN (1 0 2) (from 886 to 493 arcsec). An LED with six pairs of InGaN/GaN multiple quantum wells was successfully fabricated on the (−2 0 1) β -Ga2 O3 single crystal substrate.